A MODEL FOR DEVELOPING LEARNING SKILLS IN THE NEW NORMAL ERA TO ENHANCE DIGITAL CITIZENSHIP IN SMALL SCHOOLS UNDER THE OFFICE OF PHAYAO PRIMARY EDUCATION SERVICE AREA - Jatuporn, Watchara (Journal of Education and Innovation, 2025)
This research aimed to study learning skills in the new normal era of students in small schools, examine the enhancement of digital citizenship among students in small schools, and develop a model for improving learning skills in the new normal era to promote digital citizenship in small schools under the Office of Phayao Primary Education Service Area. The sample consisted of 234 teachers from small schools. The research instruments were questionnaires and a model evaluation form. Quantitative data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. Qualitative data were analyzed through content analysis and data classification. The research findings were as follows: 1) Learning skills in the new normal era for small schools under the Office of Phayao Primary Education Service Area comprised five skills: critical thinking, communication, collaboration, creative thinking and innovation, and information technology skills. Overall, these skills were rated at a high level. 2) Digital citizenship of students in small schools consisted of three aspects: respect for yourself and others, educate yourself and others, and protect yourself and others. Overall, these aspects were rated at a high level. 3) The model for developing learning skills in the new normal era to enhance digital citizenship in small schools under the Office of Phayao Primary Education Service Area was named "5 Skills, 3 Characteristics of Digital Citizenship in the New Normal Era (S5 REP)". It consisted of three operational components: 1) development of four learning skills, 2) five learning skills of students in the new normal era, and 3) three aspects of students' digital citizenship.